Impact of body constitution on complications following pancreaticoduodenectomy: A retrospective cohort study. (December 2017) - Ekström, Eva; Ansari, Daniel; Williamsson, Caroline; Andersson, Roland; Tingstedt, Bobby; Aronsson, Linus; Nilsson, Johan; Andersson, Bodil
Abstract: Background: Overweight, defined by body mass index (BMI), is correlated to complications following pancreaticoduodenectomy (PD). The aim of this study was to evaluate the impact of body constitution, measured with different anthropometric measures, and diabetes on complications following PD. Materials and methods: Patients who underwent PD between 2000 and 2015 at Skåne University Hospital were retrospectively included. Body mass index (BMI), body surface area (BSA) and body fat percentage (BF%) were calculated. Overweight and obesity were defined by BMI according to the WHO classification (overweight ≥25 and obesity ≥30). Values equal to or above the median value were considered as large by BSA (≥1.87) and overweight by BF% (≥29.6% (male) and ≥38.9% (female)). Main endpoints were events of postoperative pancreatic fistula (POPF), post pancreatectomy hemorrhage (PPH), delayed gastric emptying (DGE) and complications classified according to the Clavien-Dindo classification. Multivariable analysis was performed using logistic regression and a subgroup analysis on diabetic patients was performed. Results: In total 328 patients were included. The incidence of POPF grades B and C was increased among overweight and large patients defined by BMI (OR 4.16; p = 0.001), BSA (OR 2.88; p = 0.018) and BF% (OR 3.94; p = 0.001). However, the risk was not increased among diabetic patients with BMI≥25 and BMI≥30. DGE and complications classified as Clavien grade ≥3 were more common in patients defined as overweight by both BMI (OR 1.72; p = 0.024 and OR 2.63; p = 0.003, respectively) and BF% (OR 2.13; p = 0.001 and OR 2.31; p = 0.009, respectively). PPH was not more frequent in overweight or large patients. Conclusion: Body constitution has an impact on the risk of severe complications following PD. BMI, BSA and BF% can all be used to identify risk groups. The risk of developing POPF grades B and C was significantly increased in overweight and large patients, but not in patients with coexisting diabetes. Highlights: Body constitution has an impact on the risk of severe complications after PD. Overweight and large patients have an increased risk of POPF grades B and C. POPF grades B and C are not increased in diabetic patients with BMI≥25. DGE are more frequent in overweight patients. The risk of complications with Clavien grade≥3 are increased in overweight patients.